Land Utilisation and Welfare of Farmers in Sabbatical Legislation of the Book of Leviticus (2014)
Sabbatical legislation in the book of Leviticus is a set of land laws capable of promoting agricultural productivity and the welfare of the people. Previous studies on Sabbatical legislation in Leviticus have focused on land acquisition and distribution, neglecting various mistranslations that led to their misinterpretations. This anomaly changed the understanding of the concept of rest, which originally applied more to the human agentive utilisation and welfare agenda in ancient Israel. This study, therefore, re-interpreted Sabbatical legislation with particular reference to land utilisation and rest, agricultural productivity, and welfare of farmers, with a view to restoring a holistic and culture-bound translation. This study adopted Christopher Wright‟s Biblical Ecological theory, which holds that there is a link between proper land utilisation and the welfare of the people. The historical-critical method represented by Graf Wellhausen‟s Documentary hypothesis was employed to locate the progression, composition and transformation of Leviticus 25:1-7, the purposively selected text. Three documents from Food and Agriculture Organisation and extra-canonical texts, including the Mishna, Talmud and Nitzana scrolls, were consulted. Data were subjected to exegetical and descriptive analyses. Sabbatical legislation in ancient Israel has three main components, namely, land use, agricultural productivity and farmers‟ welfare. For the limited arable land mass, suffering from an unpredictable pattern of rainfall and drought and negatively affecting farmers‟ welfare, it was legislated in Leviticus 25:2 that land should rest (shabbat ‘eretz). Leviticus 25:3-4 also commanded that when land is left fallow every seventh year of cultivation and harvesting, it would be replenished and agricultural produce would be boosted. Leviticus 25:5-7 instructed abstentions from work as a result of rest for land which has positive ripple effects on man‟s physical and mental health thereby enhancing the holistic well-being of farmers. However, there was a certain omission in the earlier version by an exilic redactor who removed “in” from the phrase “you, (man) in the land shall observe (shabat) rest (Shabbat)”. This error has obscured the original motive of the Sabbatical legislation by modifying verses 2, 4 and 5, which make “the land” ‘eretz the subject of rest instead of an indirect object “in the land” be‘eretz–, thereby changing a social welfare measure for farmers to providing shabbathon ‘eretz shabat rest for the land. This modification might have been overlooked by earlier redactors who did not envisage the consequences on an agrarian community. Land was the focus of the prevailing interpretation while man became a secondary agent, which has contributed to the poor understanding of the legislation. When man replaces land as the subject of a new interpretation, the legislation will be given a better meaning and powerful people with assets and position may be restrained from exploiting and oppressing landless farmers. The importance of the new interpretation for land utilisation, agricultural productivity and farmers‟ welfare shows man, not land, as the main focus and interpreter. The reinterpretation of Sabbatical legislation in ancient Israel showed man as the primary focus of the concept. Future biblical revisions should restore the preferred translation of the text